Modified silicon material and application thereof
By coating copolymers on the surface of the silicon material and preparing modified silicon materials, the problem of volume changes and low conductivity of silicon batteries during charging and discharging is solved, and the battery performance is improved and the life of the battery is extended.
Patent Information
- Application Number
- CN202411960440.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The huge volume changes and low conductivity of silicon batteries during charging and discharging lead to rapid attenuation of lithium storage capacity, which cannot meet the actual application needs.
Modified silicon material including a core layer and a shell layer is prepared by coating the copolymer on the surface of the silicon material. The shell layer is composed of a copolymer, and the first and second monomers of the copolymer are formed by copolymerization reaction to enhance the toughness and electrochemical properties of the shell layer.
It suppresses the volume change of silicon during charging and discharging, improves electrochemical performance, extends the cycle life of the battery and improves the safety of the battery.
Smart Images

Figure CN119786559A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a modified silicon material and application thereof. Background Art
[0002] With the rapid development of mobile electronic devices, electric vehicles, and grid energy storage, the development of batteries with high energy density, high power density, long cycle life, and high safety is a research hotspot and focus in the field of energy storage today. Developing electrode materials with high capacity, high rate, and high cycle stability is an important way to achieve this goal. Silicon has attracted widespread attention due to its abundant reserves and extremely high theoretical charge capacity. However, due to its huge volume changes (greater than 300%) during charging and discharging and its inherent low conductivity, the lithium storage capacity of silicon decays rapidly during the cycle and cannot meet the needs of practical applications.
[0003] In the existing technology, researchers have adopted the method of modifying silicon to improve the huge volume change of silicon during the charging and discharging process. Currently, there are silicon oxidation modification methods, porous modification methods, alloying modification methods, and composite modification methods.
[0004] Among them, the silicon oxidation modification method is to form a stable oxide layer on the silicon surface through oxidation, which can act as a buffer layer to reduce the volume expansion of silicon during the charge and discharge process. However, the oxide layer formed by this method will affect the conductivity of silicon, thereby affecting the performance of the battery.
[0005] The alloying modification method is to form an alloy with other metals to enhance the electrochemical properties of silicon. However, the silicon alloy material may expand and contract in volume during the charging and discharging process, affecting the cycle stability of the battery.
[0006] The composite modification method is to combine silicon with carbon materials. Since carbon materials have good conductivity and mechanical stability, they can effectively alleviate the volume expansion of silicon and provide support for silicon to prevent it from breaking during charging and discharging. However, combining silicon with carbon materials may affect its intrinsic properties, such as high specific capacity. Summary of the invention
[0007] In order to suppress the huge volume change of silicon during the charge and discharge process and improve the electrochemical performance of silicon, the present invention provides a modified silicon material and application thereof.
[0008] According to one aspect of the present application, a modified silicon material is provided, the modified silicon material comprising a core layer and a shell layer, wherein the shell layer covers the core layer; the core layer comprises a silicon material; the shell layer comprises a copolymer, and the raw materials for preparing the copolymer comprise a first monomer and a second monomer; wherein the first monomer comprises one of a monomer A and a monomer B; the chemical structure of the monomer A is R1, R2, R3 are independently selected from H, -NO2, At least one of, R4 is independently selected from at least one of H and phenyl; the chemical structure of monomer B is R5~R 11 Independently selected from at least one of H and F; the second monomer includes one of oxysilane compounds, dienoic acid methyl ester compounds, unsaturated hydrocarbons, and organic acid lithium.
[0009] The present invention can suppress the huge volume change of silicon during the charge and discharge process by coating the copolymer on the surface of the silicon material, and can improve the electrochemical properties of silicon by preparing the copolymer by matching the first monomer and the second monomer. Specifically, the present invention can enhance the toughness of the shell by introducing a monomer A with a rigid benzene ring structure or a monomer B with a long chain structure, so that the shell is not easily broken by the expansion of silicon. Furthermore, by limiting the type of branched functional groups in the first monomer, the electrochemical properties of the first monomer can be improved. In addition, the introduction of the second monomer can further improve the toughness and electrochemical properties of the copolymer.
[0010] Preferably, the first monomer includes monomer A, and the chemical structural formula of monomer A is; The second monomer is an oxysilane compound, wherein the oxysilane compound includes methacryloxypropyltriethoxysilane. The sulfonate structure in monomer A can be used as a storage medium for lithium ions. Methacryloxypropyltriethoxysilane can be used as a pathway for the movement of lithium ions due to its strong electron-withdrawing ability, thereby giving the polymer a higher ionic conductivity and improving fast charging performance. In addition, the silicon-oxygen bonds in methacryloxypropyltriethoxysilane can react with hydrofluoric acid to improve the stability of silicon materials. Thus, by combining monomer A with methacryloxypropyltriethoxysilane, the silicon material can be protected from corrosion.
[0011] Preferably, calculated by molar ratio, monomer A:oxysilane compound=1-5:1.
[0012] Preferably, calculated by molar ratio, monomer A:oxysilane compound=1-3:1.
[0013] Preferably, the molecular weight of the copolymer obtained by copolymerization of monomer A and the oxysilane compound is 5,000 to 30,000.
[0014] Preferably, the first monomer includes monomer A, and the chemical structure of monomer A is The second monomer is a dienoic acid methyl ester compound, and the dienoic acid methyl ester compound includes (9Z, 12E)-octadecadienoic acid methyl ester. The imide part in monomer A has a strong electron-withdrawing part, which can form a weak covalent bond with lithium ions, thereby improving the ionic conductivity of the modified silicon material. However, due to its strong rigidity, the shell structure formed alone is easy to break. The present invention increases the flexibility of the shell by introducing the second monomer. This is because the alkyl segment and double bond in the second monomer are highly flexible, making the polymer flexible and rigid, and better inhibiting the expansion of silicon.
[0015] Preferably, calculated by molar ratio, monomer A: dienoic acid methyl ester compound = 1-6:1.
[0016] Preferably, calculated by molar ratio, monomer A: dienoic acid methyl ester compound = 1-3:1.
[0017] Preferably, the molecular weight of the copolymer obtained by copolymerization of monomer A and dienoic acid methyl ester compound is 5000-30000.
[0018] Preferably, the first monomer includes monomer A, and the chemical structure of monomer A is The second monomer is an unsaturated hydrocarbon, including allylamine and 1,3-butadiene. The introduction of flexible 1,3-butadiene can alleviate the stress concentration and structural rupture caused by the volume change of silicon materials during charging and discharging, thereby enhancing the cycle performance and life of the battery. On the other hand, the polar group nitro in the copolymer can improve the conductivity of silicon materials through physical interaction with Li+, thereby significantly improving the rate performance of the battery; and the nitro and amine groups have good flame retardant effects, which can improve the safety performance of the battery.
[0019] Preferably, calculated by molar ratio, monomer A: allylamine: 1,3-butadiene = 1-6: 1-3: 1-3.
[0020] Preferably, calculated by molar ratio, monomer A: allylamine: 1,3-butadiene = 4:1:2.
[0021] Preferably, the molecular weight of the copolymer obtained by copolymerization of monomer A and unsaturated hydrocarbon is 10,000 to 80,000.
[0022] Preferably, the first monomer includes monomer A, and the chemical structure of monomer A is The second monomer is an organic acid lithium, which includes at least one of lithium vinyl terephthalate and lithium acrylate. The organic acid lithium contains a charged group (Li +) can give the modified silicon material high ionic conductivity, wide electrochemical window and excellent chemical / electrochemical stability; on the other hand, the lithium carboxylate and lithium sulfonate groups of the copolymer will form hydrogen bonds with the hydroxyl groups on the surface of the silicon material, which can improve the adhesion between the core layer and the shell layer of the modified silicon material, help maintain the structural integrity of the silicon-carbon core, reduce the shedding of silicon particles, and thus improve the performance of the battery.
[0023] Preferably, calculated by molar ratio, monomer A: organic acid lithium = 1-4: 1-9.
[0024] Preferably, calculated by molar ratio, monomer A: organic acid lithium = 1:5-7.
[0025] Preferably, the first monomer includes monomer B, and the number of fluorine atoms N in monomer B is ≥ 1; the second monomer is an oxysilane compound, wherein the oxysilane compound includes acrylamidopropyltrimethoxysilane. The introduction of monomer B and acrylamidopropyltrimethoxysilane into the polymer can, on the one hand, form hydrogen bonds with the hydroxyl groups on the surface of the silicon material to increase the interaction between the core layer and the shell layer; on the other hand, the oxysilane compound can absorb HF in the electrolyte to prevent HF from corroding the modified silicon material and improve the rate cycling performance.
[0026] Preferably, the number of fluorine atoms N in the monomer B satisfies: 1≤N≤15. The F element in the polymer can reduce the surface energy of the electrode, thereby improving the wettability with the electrolyte and improving the rate performance.
[0027] Preferably, calculated by molar ratio, monomer B:oxysilane compound=1:1-5.
[0028] Preferably, calculated by molar ratio, monomer B:oxysilane compound=1:3-4.
[0029] Preferably, the preparation method of the copolymer comprises the following steps: mixing the first monomer, the second monomer and the organic solvent, adding an initiator, heating at 40-90° C. under argon protection, and reacting for 5-9 hours to obtain a solution I; then adding the solution I to the precipitation solvent to obtain a copolymer.
[0030] Preferably, the organic solvent includes at least one of benzene, toluene, N-methyl-2-pyrrolidone (NMP), and N,N-dimethylformamide (DMF).
[0031] Preferably, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile or dibenzoyl peroxide (BPO).
[0032] Preferably, the mass content of the added initiator is 0.1-0.9% of the total amount of the first monomer and the second monomer.
[0033] Preferably, the precipitation solvent is one of propanol, isopropanol and acetone.
[0034] Preferably, the preparation method of the modified silicon material comprises the following steps: dissolving the copolymer in an organic solvent to prepare a solution II with a mass fraction of 5 to 30%; then adding the silicon material to the solution II, stirring at 30 to 100° C. for 4 to 10 hours to obtain a solution III and spray drying the solution III to obtain the modified silicon material.
[0035] Preferably, the inlet temperature of the spray drying process is 100-200°C, and the outlet temperature is 60-90°C.
[0036] Preferably, the modified silicon material includes mesopores and micropores, wherein the pore diameter of the mesopores is 3nm to 40nm; the pore diameter of the micropores is 1nm to 2nm; and the content of the mesopores is 45 to 90%; the content of the micropores is less than 60%.
[0037] Preferably, D of the silicon material 50 The diameter of the shell layer is 4 to 10 μm, and the thickness of the shell layer is 10 to 150 nm.
[0038] Preferably, the silicon material comprises silicon carbon.
[0039] Preferably, in the silicon material, the mass ratio of silicon element to carbon element is 0.4 to 1.3.
[0040] Preferably, the specific surface area of the silicon material is 1 m 2 / g~8m 2 / g.
[0041] Preferably, the modified silicon material is coated with an amorphous carbon layer, wherein the thickness of the amorphous carbon layer is 3 to 55 nm, and the amorphous carbon content is 1 to 3%.
[0042] According to a second aspect of the present application, a negative electrode is provided, which includes the modified silicon material as described above.
[0043] According to a third aspect of the present application, a battery is provided, comprising the negative electrode as described above. DETAILED DESCRIPTION
[0044] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.
[0045] Example 1
[0046] 1. Preparation of modified silicon materials
[0047] The preparation method of the copolymer comprises the following steps: mixing the first monomer, the second monomer and the organic solvent, adding the initiator, heating at 70°C under argon protection, reacting for 8 hours to obtain solution I; then adding solution I to the precipitation solvent to obtain the copolymer. The second monomer is methacryloxypropyltriethoxysilane, and the molar ratio of the first monomer to the second monomer is 3:1. The amount of the initiator is 0.5% of the total amount of the first monomer and the second monomer.
[0048] The preparation method of the modified silicon material comprises the following steps: dissolving the copolymer in an organic solvent to prepare a solution II with a mass fraction of 20%; then adding the silicon material (silicon carbon) to the solution II, stirring at 60°C for 8 hours to obtain a solution III and spray drying the solution III to obtain the modified silicon material. The parameters of the spray drying process are: inlet temperature = 150°C, outlet temperature = 70°C; the core layer thickness of the obtained modified silicon material is 1 to 10 μm, and the shell layer thickness is 50 nm.
[0049] 2. Preparation of Lithium-ion Batteries
[0050] (1) Preparation of positive electrode sheet
[0051] The ternary material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), and conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:2:2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after drying and cold pressing processes.
[0052] (2) Preparation of negative electrode sheet
[0053] The modified silicon material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 80:9:1:10 to obtain a negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on a copper foil through a coating process, and a negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0054] (3) Selection of electrolyte
[0055] EC:DMC:DEC:FEC=20:40:30:10, LiPF6 1mol / L to prepare lithium-ion batteries.
[0056] (4) Selection of isolation membrane
[0057] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0058] (5) Preparation of lithium-ion batteries
[0059] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0060] Example 2
[0061] This embodiment refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 1 is that the first monomer used in the preparation of the modified silicon material in this embodiment is The second monomer is (9Z, 12E)-octadecadienoic acid methyl ester. Except for the above differences, the operation steps of preparing the modified silicon material and the negative electrode and lithium-ion battery using the modified silicon material in this embodiment are strictly consistent with those in Example 1.
[0062] Example 3
[0063] This embodiment refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 1 is that the first monomer used in the preparation of the modified silicon material in this embodiment is The second monomer is allylamine and 1,3-butadiene, and calculated by mass ratio, monomer A: allylamine: 1,3-butadiene = 4:1:2. Except for the above differences, the operation steps of preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this embodiment are strictly consistent with those in Example 1.
[0064] Example 4
[0065] This embodiment refers to the formula and method provided in Example 3 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 3 is that the first monomer used in the preparation of the modified silicon material in this embodiment is Except for the above differences, the operation steps of preparing the modified silicon material and the negative electrode and lithium-ion battery using the modified silicon material in this embodiment are strictly consistent with those in Example 3.
[0066] Example 5
[0067] This embodiment refers to the formula and method provided in Example 3 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 3 is that the first monomer used in the preparation of the modified silicon material in this embodiment is (CAS: 586-39-0), except for the above differences, the operation steps of preparing the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material in this embodiment are strictly consistent with those in Example 3.
[0068] Example 6
[0069] This embodiment refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 1 is that the first monomer used in the preparation of the modified silicon material in this embodiment is The second monomer is lithium vinyl terephthalate, and calculated by mass ratio, the first monomer: the second monomer = 1:6. Except for the above differences, the operation steps of preparing the modified silicon material and the negative electrode and lithium ion battery using the same in this embodiment are strictly consistent with those in Example 1.
[0070] Example 7
[0071] This embodiment refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 1 is that the first monomer used in the preparation of the modified silicon material in this embodiment is The second monomer is lithium acrylate, and calculated by mass ratio, the first monomer: the second monomer = 1:6. Except for the above differences, the operation steps of preparing the modified silicon material and the negative electrode and lithium ion battery using the same in this embodiment are strictly consistent with those in Example 1.
[0072] Example 8
[0073] This embodiment refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 1 is that the first monomer used in the preparation of the modified silicon material in this embodiment is (CAS: 16083-81-1), the second monomer is acrylamidopropyltrimethoxysilane (CAS: 57577-96-5), and calculated by mass ratio, the first monomer: the second monomer = 1:3.5. Except for the above differences, the operating steps of preparing the modified silicon material and the negative electrode and lithium ion battery using the same in this embodiment are strictly consistent with those in Example 1.
[0074] Example 9
[0075] This embodiment refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 1 is that the first monomer used in the preparation of the modified silicon material in this embodiment is The second monomer is allylamine and 1,3-butadiene, and calculated by mass ratio, the first monomer: allylamine: 1,3-butadiene = 4:1:2. Except for the above differences, the operation steps of preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this embodiment are strictly consistent with those in Example 1.
[0076] Example 10
[0077] This embodiment refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 1 is that the first monomer used in the preparation of the modified silicon material in this embodiment is The second monomer is methacryloxypropyltriethoxysilane. Except for the above differences, the operation steps of preparing the modified silicon material and the negative electrode and lithium-ion battery using the modified silicon material in this embodiment are strictly consistent with those in Example 1.
[0078] Embodiment 11
[0079] This embodiment refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium ion battery using the modified silicon material. The difference from Example 1 is that the first monomer used in the preparation of the modified silicon material in this embodiment is (CAS: 16083-81-1), the second monomer is allylamine and 1,3-butadiene, and calculated by mass ratio, the first monomer: allylamine: 1,3-butadiene = 4:1:2. Except for the above differences, the operation steps of preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this embodiment are strictly consistent with those in Example 1.
[0080] Comparative Example 1
[0081] This comparative example prepares a negative electrode and a lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that the negative electrode active material used in the preparation of the negative electrode in this comparative example is silicon carbon. Except for the above difference, the operating steps for preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 1.
[0082] Comparative Example 2
[0083] This comparative example refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium-ion battery using the same. The difference from Example 1 is that the first monomer used in this comparative example is replaced by methacryloxypropyltriethoxysilane with an equal mass fraction when preparing the modified silicon material. Except for the above differences, the operating steps for preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 1.
[0084] Comparative Example 3
[0085] This comparative example refers to the formula and method provided in Example 2 to prepare modified silicon materials and negative electrodes and lithium-ion batteries using the same. The difference from Example 2 is that the first monomer used in this comparative example is replaced by (9Z, 12E)-octadecadienoic acid methyl ester with an equal mass fraction when preparing the modified silicon material. Except for the above differences, the operating steps for preparing modified silicon materials and negative electrodes and lithium-ion batteries using the same in this comparative example are strictly consistent with those in Example 2.
[0086] Comparative Example 4
[0087] This comparative example refers to the formula and method provided in Example 3 to prepare modified silicon materials and negative electrodes and lithium-ion batteries using the same. The difference from Example 3 is that when preparing the modified silicon material, this comparative example uses equal mass fractions of allylamine and 1,3-butadiene to replace the first monomer used (wherein the mass ratio of allylamine and 1,3-butadiene remains unchanged). Except for the above differences, the operating steps for preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 3.
[0088] Comparative Example 5
[0089] This comparative example refers to the formula and method provided in Example 6 to prepare the modified silicon material and the negative electrode and lithium-ion battery using the same. The difference from Example 6 is that the first monomer used in this comparative example is replaced by lithium vinyl terephthalate with an equal mass fraction when preparing the modified silicon material. Except for the above differences, the operating steps for preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 6.
[0090] Comparative Example 6
[0091] This comparative example refers to the formula and method provided in Example 8 to prepare modified silicon materials and negative electrodes and lithium-ion batteries using the same. The difference from Example 8 is that in this comparative example, acrylamidopropyltrimethoxysilane of an equal mass fraction is used to replace the first monomer used when preparing the modified silicon material. Except for the above differences, the operating steps for preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 8.
[0092] Comparative Example 7
[0093] This comparative example refers to the formula and method provided in Example 1 to prepare the modified silicon material and the negative electrode and lithium-ion battery using the same. The difference from Example 1 is that the methacryloxypropyltriethoxysilane used in the preparation of the modified silicon material is replaced by the first monomer with an equal mass fraction. Except for the above differences, the operating steps for preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 1.
[0094] Comparative Example 8
[0095] This comparative example refers to the formula and method provided in Example 2 to prepare the modified silicon material and the negative electrode and lithium-ion battery using the same. The difference from Example 2 is that the (9Z, 12E)-octadecadienoic acid methyl ester used in this comparative example is replaced by the first monomer with an equal mass fraction when preparing the modified silicon material. Except for the above differences, the operating steps for preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 2.
[0096] Comparative Example 9
[0097] This comparative example refers to the formula and method provided in Example 3 to prepare modified silicon materials and negative electrodes and lithium-ion batteries using the same. The difference from Example 3 is that in this comparative example, the allylamine and 1,3-butadiene used are replaced by the first monomer with equal mass fractions when preparing the modified silicon material. Except for the above differences, the operating steps for preparing modified silicon materials and negative electrodes and lithium-ion batteries using the same in this comparative example are strictly consistent with those in Example 3.
[0098] Comparative Example 10
[0099] This comparative example refers to the formula and method provided in Example 8 to prepare the modified silicon material and the negative electrode and lithium-ion battery using the same. The difference from Example 8 is that the acrylamidopropyltrimethoxysilane used in the preparation of the modified silicon material in this comparative example is replaced by the first monomer with an equal mass fraction. Except for the above difference, the operating steps for preparing the modified silicon material and the negative electrode and lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 8.
[0100] Test Case
[0101] 1. Test subjects
[0102] The modified silicon material prepared in Example 1 and Comparative Example 1, and the negative electrode and lithium-ion battery using the same.
[0103] 2. Test Method
[0104] (1) First coulombic efficiency: At 25°C, charge the lithium-ion battery to 4.2V at a constant current and constant voltage rate of 0.33C, let it stand for 10 minutes, then discharge the lithium-ion battery to 2.5V at a constant current rate of 0.33C, let it stand for 10 minutes, and calculate the first coulombic efficiency of the lithium-ion battery. Calculate the first coulombic efficiency (first efficiency) according to the following formula:
[0105] First coulombic efficiency (%) = total capacity of lithium-ion battery discharged at 0.33C for the first time / total capacity of lithium-ion battery charged at 0.33C for the first time × 100%
[0106] (2) Capacity retention rate after 1200 cycles at room temperature at 1C / 1C: At 25°C, charge the lithium-ion battery to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and let it stand for 10 minutes. Then, discharge the lithium-ion battery to 2.5V at a constant current rate of 1C, and let it stand for 10 minutes. This is considered one charge and discharge cycle. Perform charge and discharge cycles of the lithium-ion battery for 1200 cycles according to the above method, and calculate the capacity retention rate after 1200 cycles of charge and discharge cycles of the lithium-ion battery at 1C / 1C. Calculate the capacity retention rate according to the following formula:
[0107] Capacity retention rate of lithium-ion battery after N cycles (%) = (discharge capacity of Nth cycle / first discharge capacity) × 100%, N is the number of cycles of lithium-ion battery
[0108] (3) 1C / 10C discharge capacity retention rate: The divided lithium-ion battery was charged to 4.2V at 1C rate at 25°C, with a cut-off current of 0.05C; left to stand for 10 min; then the lithium-ion battery was discharged to 2.5V at 1C rate, and its discharge capacity Q1C was recorded as the initial discharge capacity; then the lithium-ion battery was charged to 4.2V at 1C rate at 25°C, with a cut-off current of 0.05C; left to stand for 10 min; then the fully charged battery was discharged to 2.5V at 10C rate, and its discharge capacity Q10C was recorded; the discharge capacity retention rate of the lithium-ion battery at 1C / 10C rate was calculated according to the following formula:
[0109] Discharge capacity retention rate (%)=discharge capacity at 10C rate Q10C / discharge capacity at 1C rate Q1C×100%.
[0110] (4) Room temperature 6C rate performance - constant current charging ratio: At 25°C, the lithium-ion battery was discharged at a constant current rate of 1C to 2.5V, and then left to stand for 10 minutes. Then, the lithium-ion battery was charged at a constant current and constant voltage rate of 6C to 4.2V, with a cut-off current of 0.05C. After standing for 10 minutes, the constant current charging capacity Q1 and the constant current and constant voltage charging total capacity Q2 of the lithium-ion battery were recorded. The constant current charging ratio of the 6C rate charging was calculated according to the following formula:
[0111] 6C rate charging constant current charging ratio = constant current charging capacity Q1 / constant current constant voltage charging total capacity Q2×100%
[0112] (5) Battery cell thermal runaway ARC test: Start the ARC adiabatic thermal runaway test (the test sample is heated from room temperature to 45±2℃ in the chamber. After 90 minutes, the battery temperature rise rate is detected. If the temperature rise exceeds 0.2℃ within 10 minutes (i.e., SHR>0.02℃ / min), it is considered that a self-heating reaction occurs inside the battery. Maintain an adiabatic environment until the battery thermal runaway occurs; if the temperature rise does not exceed 0.2℃ within 10 minutes (i.e., SHR≤0.02℃ / min) (Self-heating Rate, SHR, self-heating temperature rise rate), continue to the next step temperature rise test; each temperature step is 5℃, and the steps are repeated on each step. The ARC test temperature range is 45℃~300℃, the self-heating starting temperature is T1 (temperature rise rate SHR>0.02℃ / min), and the thermal runaway starting temperature is T2 (temperature rise rate SHR>1℃ / min).
[0113] 3. Test results and analysis
[0114] The test results of this test example are shown in Table 1 and Table 2. It can be seen from the test data of Examples 1 to 11 and Comparative Examples 1 to 10 that different combinations of the first monomer and the second monomer will have different effects, thereby changing the first coulombic efficiency, cycle capacity retention rate, and rate performance of the battery using the corresponding modified silicon material. In addition, it can be seen from the test data of Table 2 that the modified silicon materials provided in Examples 1 to 8 all have good flame retardant effects and can improve battery safety performance. Among them, the modified silicon material provided in Example 1 has the best flame retardant performance.
[0115] Among them, it can be seen from Examples 1 to 11 and Comparative Examples 1 to 10 that the sulfonate structure in monomer A is matched with an oxysilane compound (methacryloxypropyltriethoxysilane) to have a higher first coulombic efficiency, which means that in the first charge and discharge process of the lithium battery, the efficiency of converting electrical energy into chemical energy is higher, which helps to improve the energy density of the battery, thereby extending the battery life. Further, when monomer A has an imide and is matched with a dienoic acid methyl ester compound ((9Z, 12E)-octadecadienoic acid methyl ester) or monomer B is matched with an oxysilane compound, the rate performance of the battery can be enhanced, which helps to improve the rapid charge and discharge capability of the battery. When the nitro-containing monomer A is matched with an unsaturated hydrocarbon (allylamine, 1,3-butadiene) or the sulfonic acid structure-containing monomer A is matched with an organic acid lithium, the first coulombic efficiency, cycle capacity retention rate, and rate performance are all maintained at a relatively good level, which helps to extend the battery's service life, battery life, and improve the safety of the battery.
[0116] Therefore, the data of this test example can confirm that by coating the copolymer on the surface of the silicon material, the huge volume change of silicon during the charge and discharge process can be suppressed, and by preparing the copolymer by combining the first monomer and the second monomer, the electrochemical performance of silicon can be improved.
[0117] Table 1. Test results of this test case
[0118]
[0119] Table 2. Test results of the battery cell thermal runaway ARC test in this test case
[0120] Group <![CDATA[The self-heating starting temperature is T1]]> <![CDATA[Thermal runaway starting temperature T2]]> Example 1 105.5℃ 159.8℃ Example 2 103.2℃ 158.1℃ Example 3 100.9℃ 155.2℃ Example 4 100.1℃ 153.8℃ Example 5 100.2℃ 150.8℃ Example 6 102.2℃ 154.1℃ Example 7 101.3℃ 155.9℃ Example 8 103.3℃ 157.9℃ Comparative Example 1 90.7℃ 141.8℃
[0121] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A modified silicon material, characterized in that: The modified silicon material comprises a core layer and a shell layer, wherein the shell layer covers the core layer; the core layer comprises silicon material; the shell layer comprises a copolymer, and the raw materials for preparing the copolymer comprise a first monomer and a second monomer; Wherein, the first monomer includes one of monomer A and monomer B; The chemical structural formula of the monomer A is R1, R2, R3 are independently selected from H, -NO2, At least one of, R4 is independently selected from at least one of H and phenyl; The chemical structural formula of the monomer B is R5~R 11 At least one independently selected from H and F; The second monomer includes one of an oxysilane compound, a diene acid methyl ester compound, an unsaturated hydrocarbon, and an organic acid lithium.
2. The modified silicon material according to claim 1, characterized in that: The first monomer includes the monomer A, and the chemical structure of the monomer A is The second monomer is the oxysilane compound, wherein the oxysilane compound includes methacryloxypropyltriethoxysilane.
3. The modified silicon material according to claim 1, characterized in that: The first monomer includes the monomer A, and the chemical structure of the monomer A is The second monomer is the dienoic acid methyl ester compound, and the dienoic acid methyl ester compound includes (9Z, 12E)-octadecadienoic acid methyl ester.
4. The modified silicon material according to claim 1, characterized in that: The first monomer includes the monomer A, and the chemical structure of the monomer A is At least one of the following: the second monomer is the unsaturated hydrocarbon, and the unsaturated hydrocarbon includes allylamine and 1,3-butadiene.
5. The modified silicon material according to claim 1, characterized in that: The first monomer includes the monomer A, and the chemical structure of the monomer A is The second monomer is the organic acid lithium, and the organic acid lithium includes at least one of lithium vinyl terephthalate and lithium acrylate.
6. The modified silicon material according to claim 1, characterized in that: The first monomer includes the monomer B, and the number of fluorine atoms N in the monomer B is ≥1; the second monomer is the oxysilane compound, wherein the oxysilane compound includes acrylamidopropyltrimethoxysilane.
7. The modified silicon material according to claim 1, characterized in that: The modified silicon material includes mesopores and micropores, wherein the pore diameter of the mesopores is 3nm-40nm; the pore diameter of the micropores is 1nm-2nm; and the content of the mesopores is 45-90%; the content of the micropores is less than 60%.
8. The modified silicon material according to any one of claims 1 to 7, characterized in that: The D of the silicon material 50 The diameter of the shell layer is 4 to 10 μm, and the thickness of the shell layer is 10 to 150 nm.
9. A negative electrode, characterized in that The negative electrode comprises the modified silicon material according to any one of claims 1 to 8.
10. A battery, characterized in that: The battery comprises the negative electrode as claimed in claim 9.
Citation Information
Patent Citations
Negative pole active material for lithium secondary battery and lithium secondary battery comprising same
CN104335395A
Silicon anode material and preparation method thereof and anode and lithium ion battery containing silicon anode material
CN106159215A
Preparation method of organic silicon nano protective coating of modulation structure
CN107686986A
Silicon-based negative electrode material and preparation method thereof
CN108933245A
Silicon composite negative electrode material, preparation method thereof and secondary battery
CN117239089A